Whole Grain Qingke Attenuates High-Fat Diet-Induced Obesity in Mice With Alterations in Gut Microbiota and Metabolite Profile - Li, Xipu; Suo, Jingqi; Huang, Xinguo; Dai, Huifen; Bian, Hongwu; Zhu, Muyuan; Lin, Weiqiang; Han, Ning (Frontiers in Nutrition, 2021)
Whole grain Qingke (WGQK) displays anti-obesity and lipid-lowering properties; however, the underlying mechanism remains elusive. This study investigated the alteration of gut microbiota composition and metabolite profile induced by WGQK intervention in mice through the integration of 16S ribosomal RNA (rRNA) sequencing and an untargeted metabolomics study. C57BL/6J male mice were fed a normal control diet (NC), high-fat diet (HFD), and HFD plus 30% WGQK (HFD+QK) for 16 weeks. The WGQK intervention decreased body weight gain, glucose tolerance, and serum lipid levels, and alleviated liver function damage induced by HFD. Moreover, WGQK changed gut microbiota composition and enriched specific genera such as Akkermansia, Bifidobacterium, and Lactobacillus. Fecal metabolomics analysis indicated that WGQK enhanced the abundance of tryptophan metabolism-related metabolites (indole, 3-indoleacetic acid, indole acetic acid (IAA), 5-hydroxyindole-3-acetic acid), histidine metabolism-related metabolites (histamine), and some unsaturated fatty acids (oleic acid, 9,10-dihydroxy-12Z-octadecenoic acid, and alpha-linolenic acid). Spearman correlation analysis revealed that these metabolites were negatively correlated with obesity-related parameters and positively correlated with the gut genera enriched by WGQK. Moreover, WGQK promoted the expression of Cholesterol 7α-hydroxylase (CYP7A1) responsible for primary bile acids production, accompanied by a decline in intestinal FXR-FGF15 expression levels. The transcript levels of two genes associated with lipogenesis, such as lipid fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) were also decreased in the HFD+QK group. Overall, our results suggest interactions between gut microbial shifts and host amino acid/lipid metabolism, and shed light on the mechanisms underlying the anti-obesity effect of WGQK.